Organic and inorganic fertilizer for vegetable production under tropical conditions - Alimi, T.; Ajewole, O.C.; Olubode-Awosola, O.O.; Idowu, E.O. (2007)
The use of commercial organic fertilizer is being encouraged in place of inorganic fertilizer in soil fertility improvement in Oyo State of Nigeria. This study was designed to determine if switching to from inorganic to organic fertilizer could be profitable. We took a case study of users of commercial organic fertilizer (UCOF) and users of inorganic fertilizer (UIF) in vegetable production. Nested sampling technique was used in selecting UCOF and UIF. Primary data on quantities and prices of vegetable production inputs and output were collected and analysed using descriptive and inferential statistics, partial budgetary technique and importance ranking. Results indicated both the UCOF and UIF used less than the recommended quantities of fertilizer and obtained less than the optimal yield. However, the UCOF on the average used more level of organic fertilizer that supply more soil nutrient though at higher cost. Yet they obtained higher vegetable yield (9169 kg?ha-1) and a marginal rate of return of 229%. However, either a marginal 2.6% decrease in each of yield or price of vegetable or a 32.4% increase in price of commercial organic fertilizer will make commercial organic fertilizer technology not superior to inorganic fertilizer. The identified constraints to the use of commercial organic fertilizer by UIF in descending order of importance are offensive odour, doubtful efficacy, heavy weed infestation, unavailability and bulkiness of commercial organic fertilizer which if eliminated will boost the demand for and allow the enjoyment of the additional benefits of commercial organic fertilizer.